2019
DOI: 10.1186/s13071-019-3290-5
|View full text |Cite
|
Sign up to set email alerts
|

Entomological assessment of the transmission following recrudescence of onchocerciasis in the Comoé Valley, Burkina Faso

Abstract: BackgroundOnchocerciasis, or river blindness, is a dermal filariasis caused by infection with the nematode parasite Onchocerca volvulus, transmitted to humans through the bites of blackflies of the genus Simulium. Despite the decade-long West African Regional Programme for the Elimination of Onchocerciasis, involving the mass administration of ivermectin to populations in endemic areas, recrudescence has occurred. An example is in the Cascades Region of south-west Burkina Faso where the resumption of transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
3
26
1
Order By: Relevance
“…In the Comoé basin, retrospective analysis of recrudescence suggested that long-range vector movement was responsible, although immigration of infected people from outside the basin was not excluded. Ongoing transmission was confirmed via entomological assessments at 4/4 capture points (Koala et al, 2017;Koala et al, 2019). The second Burkina Faso report investigated microfilariaepositive individuals in the Upper Mouhoun, Nakambé , and Nazinon river basins and found all but 1 of the 31 infected individuals recently resided in neighboring Cô te d'Ivoire (Nikièma et al, 2018).…”
Section: Delineating Transmission Zones For Sustainable Onchocerciasimentioning
confidence: 92%
See 2 more Smart Citations
“…In the Comoé basin, retrospective analysis of recrudescence suggested that long-range vector movement was responsible, although immigration of infected people from outside the basin was not excluded. Ongoing transmission was confirmed via entomological assessments at 4/4 capture points (Koala et al, 2017;Koala et al, 2019). The second Burkina Faso report investigated microfilariaepositive individuals in the Upper Mouhoun, Nakambé , and Nazinon river basins and found all but 1 of the 31 infected individuals recently resided in neighboring Cô te d'Ivoire (Nikièma et al, 2018).…”
Section: Delineating Transmission Zones For Sustainable Onchocerciasimentioning
confidence: 92%
“…Data from Burkina Faso showed a significant delay between cessation of interventions and recrudescence (Koala et al, 2017;Koala et al, 2019), suggesting that the predicted time frames for recrudescence modeled by McCulloch et al (2017) are realistic. Such delays are not unexpected considering that parasite invasion may initiate transmission at a low level, and transmission takes time to become detectable.…”
Section: Models Incorporating Population Genetics To Estimate Risk Ofmentioning
confidence: 96%
See 1 more Smart Citation
“…Once available and validated, and provided the geographically relevant population genetic data are 450 available, such a model will allow to quantitate the risk associated with stopping interventions in one 451 geographic area meeting WHO guideline criteria when 'neighbouring' areas do not. Recrudescence could be attributable in some areas to long-range migration of infected flies from Côte 459 d'Ivoire, although recrudescence due to undetected infections in the Comoé river valley was not excluded 460 (Koala et al, 2017;Koala et al, 2019). With the methods established here, analysis of parasites from 461…”
Section: Implications Of Population Structure For Decisions To Stop Imentioning
confidence: 95%
“…Impacts of vector control were investigated by UOEP by measuring changes in the aggregate values of ABR in each focus. Typically, biting data from human landing catches (HLCs) carried out in 14 catching sites along the relevant river system in a focus during the 4-5 months pertaining to the major transmission season (at frequencies of 2 days per week) were used to make these focus-level ABR calculations using the calculation methods described in 69 .…”
Section: Datamentioning
confidence: 99%